(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2021)
This paper focuses on the relationship between cinematic stardom and aging, through the analysis of exemplary figures in in post-World War II Italy. Within a scenario in which sexualization pervades the entire media system, the decline of the star allows us to look at the female body as a mirror of transformations related to gender identities, new mass consumption, generational models, and social norms. Against this backdrop, the contribution analyses the public discourse on aging which emerges on the pages of the magazine «Oggi», looking particularly at the representation of two emblematic figures: Greta Garbo and Marlene Dietrich.